2019
DOI: 10.1111/jcmm.14632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gingiva‐derived and bone marrow mesenchymal stem cells for osteogenesis

Abstract: Presently, bone marrow is considered as a prime source of mesenchymal stem cells; however, there are some drawbacks and limitations. Compared with other mesenchymal stem cell (MSC) sources, gingiva‐derived mesenchymal stem cells (GMSCs) are abundant and easy to obtain through minimally invasive cell isolation techniques. In this study, MSCs derived from gingiva and bone marrow were isolated and cultured from mice. GMSCs were characterized by osteogenic, adipogenic and chondrogenic differentiation, and flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…Whether this relates to bona fide differences in therapeutic efficacy between MSCs derived from different tissues is unclear. MSCs are defined by the characteristics of self-renewal and multi-potent differentiation; however, cells from different strains of mice [43], different tissues [44], and tissue sites [45] within mice, and even subpopulations within a single tissue [46], show variability in their differentiation potential and associated cell-surface markers. The multi-potent MSCs used in the current study had poorer adipogenic compared with their osteo-and chondro-genic ability, and despite being~90% positive for the MSC marker Sca-1 (similar to previous OAtherapeutic studies using MSCs from bone marrow [43] or adipose tissue [23,24]), they had only modest CD29 expression and were negative for CD105.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this relates to bona fide differences in therapeutic efficacy between MSCs derived from different tissues is unclear. MSCs are defined by the characteristics of self-renewal and multi-potent differentiation; however, cells from different strains of mice [43], different tissues [44], and tissue sites [45] within mice, and even subpopulations within a single tissue [46], show variability in their differentiation potential and associated cell-surface markers. The multi-potent MSCs used in the current study had poorer adipogenic compared with their osteo-and chondro-genic ability, and despite being~90% positive for the MSC marker Sca-1 (similar to previous OAtherapeutic studies using MSCs from bone marrow [43] or adipose tissue [23,24]), they had only modest CD29 expression and were negative for CD105.…”
Section: Discussionmentioning
confidence: 99%
“…The results of differentiation were confirmed with Alizarin Red S staining to detect calcified deposits in culture, alkaline phosphatase (ALP) activity assay, and gene expression analysis of bone specific markers-Runx2 (Runt-related transcription factor 2), collagen I, ALP, osteocalcin (OCN), and bone sialoprotein (BSP) [22,25,28,29,32,[35][36][37]. Moreover, GMSCs exhibited higher osteogenic potential than BM-MSCs, as indicated by Sun et al [36].…”
Section: Stemness Properties and Differentiation Ability Of Gmscsmentioning
confidence: 65%
“…Osteogenic differentiation was carried out in a number of studies by conducting GMSCs culture in osteoinductive medium with addition of dexamethasone, ascorbic acid, and β-glycerophosphate (among others) [22,25,28,29,32,[35][36][37]. The results of differentiation were confirmed with Alizarin Red S staining to detect calcified deposits in culture, alkaline phosphatase (ALP) activity assay, and gene expression analysis of bone specific markers-Runx2 (Runt-related transcription factor 2), collagen I, ALP, osteocalcin (OCN), and bone sialoprotein (BSP) [22,25,28,29,32,[35][36][37]. Moreover, GMSCs exhibited higher osteogenic potential than BM-MSCs, as indicated by Sun et al [36].…”
Section: Stemness Properties and Differentiation Ability Of Gmscsmentioning
confidence: 99%
“…Since the first successful isolation by Zhang et al, several protocols have been reported to culture the GMSCs with a description of their characteristics [43,44]. In the immunophenotypic analysis, GMSCs are positive for classical MSC markers including CD29, CD44, CD73, CD90, and CD105 while negative for hematopoietic lineage cell markers such as CD14, CD34, and CD45 [45,46]. They can self-renew while maintaining the long-term proliferative capacity with a faster population doubling time compared to BM-MSCs [47,48].…”
Section: Gingiva-derived Stem Cells (Gmscs)mentioning
confidence: 99%